Rare Earth Metal Complexes of N-Phosphonomethyl Glycin - Pangunoori, Ramesh; Ram, Kashi (Asian Journal of Chemistry, 2010)
Stability constants of binary complexes of the type M–A, where M = Pr(III), Nd(III), Gd(III) and A = N-phosphonomethyl glycine have been determined in aqueous medium at 303K and 0.10 M (KNO3) ionic strength by using Irving-Rossotti pH titration technique.